A vueltas con la eterna pregunta: ¿Para qué sirve un criminólogo? Las (posibles) salidas profesionales de la criminología - Cámara Arroyo, Sergio (Archivos de criminología, seguridad privada y criminalística, 2020)
This brief article is structured in two different parts, although without continuity solution given the unitary theme: the first part constitutes a criticism of the poor implementation of the profession of criminologist in current justice systems; The second part is dedicated to the study of the criminologist's possibilities of job placement in different areas, from his participation in the criminal process as an expert witness, to his possible competences in the field of private business or his conjunction with other sciences such as criminalistics and prison law.